2017
DOI: 10.1186/s13063-017-2199-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-trimoxazole versus azithromycin for the treatment of undifferentiated febrile illness in Nepal: study protocol for a randomized controlled trial

Abstract: BackgroundUndifferentiated febrile illness (UFI) includes typhoid and typhus fevers and generally designates fever without any localizing signs. UFI is a great therapeutic challenge in countries like Nepal because of the lack of available point-of-care, rapid diagnostic tests. Often patients are empirically treated as presumed enteric fever. Due to the development of high-level resistance to traditionally used fluoroquinolones against enteric fever, azithromycin is now commonly used to treat enteric fever/UFI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Most of the participants in our study responded that they had used at least one antibiotic prior to the hospital visit, and most ST patients were given antibiotics against typhoid fever. UFIs in Nepal are empirically treated as presumed enteric fever [47]. Since enteric fever is endemic to the country and similar nonspecific clinical presentations are observed in enteric fever and ST patients, it is apparent for a clinician or pharmacist to have recommended antibiotics against enteric fever.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the participants in our study responded that they had used at least one antibiotic prior to the hospital visit, and most ST patients were given antibiotics against typhoid fever. UFIs in Nepal are empirically treated as presumed enteric fever [47]. Since enteric fever is endemic to the country and similar nonspecific clinical presentations are observed in enteric fever and ST patients, it is apparent for a clinician or pharmacist to have recommended antibiotics against enteric fever.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin was taken into consideration as the most frequently used prescribed antibiotic, followed by piperacillin/tazobactam. In a similar fashion, several studies undertaken in different healthcare settings in Nepal demonstrated that azithromycin is the most frequently prescribed antibiotic in outpatient departments [ 44 46 ], probably due to its high availability, safety, and affordability. Regarding ceftriaxone and levofloxacin, the significant association of adherence to treatment guidelines was in alignment with previous findings observed in Cape Town Metro District, South Africa [ 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…We conducted a parallel-group, double-blind, randomized controlled trial of SXT vs azithromycin for the treatment of UFI in Nepal at Patan Hospital and Civil Services Hospital in the Kathmandu Valley, Nepal. [ 29 ] The study protocol was reviewed and approved by the Ethics Committee of the Nepal Health Research Council and the Oxford Tropical Research Ethics Committee, United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we conducted a randomized, double-blind comparison of azithromycin vs SXT for the treatment of UFI in Nepal. We hypothesized [ 29 ] that azithromycin would be superior to SXT for the treatment of patients with UFI and sterile blood cultures but that the 2 drugs would be noninferior to one another for the treatment of blood culture–confirmed enteric fever.…”
mentioning
confidence: 99%